A new species of Sesioctonus Viereck (Hymenoptera, Braconidae, Agathidinae) from Peru - Sulca , Lidia (2023)
A new species of Sesioctonus (Braconidae: Agathidinae), Sesioctonus alvaradae sp. nov. from Peru, is described and illustrated. With the addition of this new species, Sesioctonus genus has 36 species.Publicación registrada en Zoobank/ZooBank article registered:LSIDurn:lsid:zoobank.org:pub:27DF6B6F-86FD-4E30-8D13-ED78ACFE0B3EActo nomenclatural/nomenclatural act:Sesioctonus alvaradae Sulca, 2023LSIDurn:lsid:zoobank.org:act:BF4457F1-FEEF-4A50-B51B-AEE728B368C9